Analisa Keandalan Transformator Distribusi Menggunakan Weibull Distribution di Wilayah ULP Rungkut Kota Surabaya - Adi Satrio, Aisahdan; Slamet, Puji; Sarwo Widagdo, Reza (Jurnal FORTECH, 2021)
The reliability of the electric power system is very important in the continuity of the supply of electrical energy to the load. One of the important parts in the electric power system is the transformer. Maintaining the reliability of the transformer is an effort to make electrical energy channeled properly. For this reason, efforts are needed to evaluate whether the transformer is in good condition or not by using the Weibull distribution. By looking at the average failure rate, the MTTF value is used as a benchmark for reliability. It is based on the number of disturbances that cause the transformer to fail to operate. The results of the reliability analysis with the Weibull distribution on distribution transformers in the Rungkut ULP area during the time span from 2019, 2020, 2021 obtained an average failure rate of 18.321894% per year, with an MTTF value of 0.054579 per year, so the value reliability obtained 0.981. So according to Croanbach alpha, this value belongs to a very reliable level.